Validação de indicadores de saúde mental e sua contribuição para práticas avaliativas de serviços de Atenção Psicossocial - Alves, Poliana Farias (2019)
The Psychosocial Care Centers (CAPS) present themselves as points of attention that, among other actions, have a primary function of promoting social inclusion and psychosocial rehabilitation of people with mental suffering. The expansion of these services throughout the Brazilian territory, in its various modalities, culminated in the need to evaluate its actions. Despite the importance and growth of evaluative processes in the last decade, there is still a scarcity of results derived from these evaluations, both in academia and in the practical field. Thus, there is an imperative need to invest in the construction of mental health assessment indicators based on methodologies that emphasize and support the needs of the actors in these services of great importance in the context of Brazilian mental health. Thus, the objective of this study was to validate mental health indicators that contribute to the practice of the evaluation of Psychosocial Care services. It is an evaluative study of validation, with qualitative participatory approach. The same was done in four steps. The first step was to systematize the bibliographic review to track community mental health indicators at the national and international levels. The second stage was the translation, pre-selection and organization of the indicators in structure, process and result. In the 3rd stage, groups of validation of the indicators were carried out from specialists in mental health. The structure and process indicators were validated by workers and coordinators / managers of the Centers for Psychosocial Care through the RAND / UCLA Appropriateness Method. The outcome indicators were validated by users and former users of the Psychosocial Care Centers through focus groups. The last step was the construction of a tool with the theoretical basis and guidance on the use of validated indicators. The data collection was carried out in the city of Pelotas, Rio Grande do Sul, from June to July 2018 and counted on the participation of 10 workers, 5 coordinators / managers and 6 users and former users of mental health services of the region. To analyze the validation data using the RAND method, the medians of the scores attributed to the indicators were calculated and those with scores of 7-9 points were selected. The outcome indicators, analyzed by the users, were selected through the level of importance (important result or not important result) for users of the services. The qualitative data from the discussions of all the participants about the indicators were ordered and later articulated with the theoretical reference of the Quality Assessment of Avedis Donabedian. This was approved by the Ethics and Research Committee under verdict n.2,639,431. As a result, 6 structure, 12 process and 6 result indicators were validated, all of them presented with the name of the indicator, the definition, the objective, the form of calculation or obtaining, the source and the frequency of collection of data. Thus, the methods used proved to be appropriate for the validation of both quantitative and qualitative quality indicators and present a high potential to contribute to the evaluation processes in the field of mental health.